Crystallization and preliminary X-ray diffraction studies of BnSP-6, a myotoxic phospholipase A2 from Bothrops neuwiedi venom - Fontes, Marcos R. M. [UNESP]; Monteiro, Luiz E. [UNESP]; Soares, Andreimar M.; Rodrigues, Veridiana M.; Da Silva, Reinaldo J. [UNESP]; Giglio, José R. (My University, 2000)
BnSP-6 (myotoxin I) is a phospholipase A2 homologue isolated from Bothrops neuwiedi pauloensis venom. Crystals of BnSP-6 were obtained which diffracted X-rays to 2.5 Å resolution using a synchrotron radiation source at room temperature and belong to space group P3121. The unit cell dimensions are a=b=57.7, c=131.1 Å. The structure was solved by molecular replacement using the coordinates of bothropstoxin I from B. jararacussu venom. There are two molecules in the asymmetric unit.